A novel body frame based approach to aerospacecraft attitude tracking. (September 2017) - Ma, Carlos; Chen, Michael Z.Q.; Lam, James; Cheung, Kie Chung
Abstract: In the common practice of designing an attitude tracker for an aerospacecraft, one transforms the Newton-Euler rotation equations to obtain the dynamic equations of some chosen inertial frame based attitude metrics, such as Euler angles and unit quaternions. A Lyapunov approach is then used to design a controller which ensures asymptotic convergence of the attitude to the desired orientation. Although this design methodology is pretty standard, it usually involves singularity-prone coordinate transformations which complicates the analysis process and controller design. A new, singularity free error feedback method is proposed in the paper to provide simple and intuitive stability analysis and controller synthesis. This new body frame based method utilizes the concept of Euleraxis and angles to generate the smallest error angles from a body frame perspective, without coordinate transformations. Global tracking convergence is illustrated with the use of a feedback linearizing PD tracker, a sliding mode controller, and a model reference adaptive controller. Experimental results are also obtained on a quadrotor platform with unknown system parameters and disturbances, using a boundary layer approximated sliding mode controller, a PIDD controller, and a unit sliding mode controller. Significant tracking quality is attained. Abstract : Highlights: A body-frame based aerospacecraft attitude controller design method is proposed. The method utilizes the feedback of the attitude error Euleraxis-angle. The method ensures a shortest-rotation attitude tracking. The body-frame equations can be used directly in our design method. Satisfactory tracking quality is attained in simulations and on a quadrotor UAV.